Inhibition of Human Neutrophil Extracellular Trap (NET) Production by Propofol and Lipid Emulsion - Meier, Angela; Chien, Jason; Hobohm, Laura; Patras, Kathryn Ann; Nizet, Victor; Corriden, Ross (Frontiers in Pharmacology, 2019)
Uncontrolled bacteremia takes more human lives than any cancer. Neutrophil granulocytes are essential in containing and killing bacteria, and their repertoire includes producing Neutrophil Extracellular Traps (NETs), DNA-based net-like structures with antimicrobial activity. In sepsis, however, NETs are also known to worsen disseminated coagulation, promote venous thrombosis and are associated with worse outcomes in infections. Here, we describe how physiologic concentrations of the commonly used sedative propofol impair NET production by human neutrophils. Drugs commonly administered in the ICU may impact the inflammatory response to either worsen or improve clinical outcomes and may therefore be considered for additional therapeutic effects if clinical studies confirm such findings.